Novel carbon microtube based solid acid from pampas grass stick for biodiesel synthesis from waste oils - Yingxia Shi; Xuezheng Liang (Journal of Saudi Chemical Society)
The novel porous carbon based solid acid with microtube structure was synthesized via the facile carbonization and sulfonation of the pampas grass stick raw material. The carbon structure could be easily adjusted via the pampas grass stick with different maturity. The carbon microtube based solid acid was characterized by FT-IR, SEM, TG and BET. The acidic properties of the solid acid could be adjusted easily from the carbonization or sulfonation. The solid acid showed high activities for the biodiesel synthesis from fried cooking oils with total yield over 99%. Both the esterification of FFAs and transesterification of triglycerides were carried out completely under mild condition using the novel solid acid. The microtube structure provided the easily accessible acidic sites to bulky hydrophobic triglycerides and separated polar byproduct water from active sites. The facile synthetic process, microtube structure, high activity, stability and reusability made the novel solid acid one of the best choice for biodiesel synthesis from waste oils. Keywords: Carbon microtube based solid acid, Pampas grass stick, Waste oil, Biodiesel synthesis